The liability of the producer of false halal products under product liability law - Amin, Naemah; Abdul Aziz, Norazlina (Canadian Center of Science and Education, 2015)
The ultimate physical outcomes of compliance with halal requirements in Islamic production are high quality and safe products. The producers or suppliers, who claim that their products are halal but in actual fact are not halal, are subject to criminal sanctions under relevant laws in Malaysia. The question arises as to whether the producers of non-halal products can also be liable for physical or emotional injury caused to the victims of such products. This paper aims to explore the potential liability of the producer and supplier of false halal products under the product liability law which generally concerns with providing protection to consumers against unsafe products. The paper specifically examines the provisions of strict liability for defective products under Part X of Consumer Protection Act 1999 (CPA). The main questions to be answered are whether non-halal products can be considered as ‘defective’ and what kind of injury can be recovered by the victims. The findings of this study provide insights to producers and suppliers on the civil liability for supplying supposedly halal products and recognition of consumer right of redress for injury caused by non-halal products.